Project Office as a Promising Management Tool in the Financial Market - Petrovich Garnov, Andrey (2021)
In the context of a dynamic external environment and continuously emerging global challenges, one of the most important issues for any corporation is its effective functioning and development in the long term. The current state of the markets is characterized by constantly changing external factors that have a significant impact on the position of the corporation in the market. Obviously, in order to carry out their activities, corporations must adapt to the impact of environmental factors by improving the structure of the organization and the quality of management. At the same time, the best results are achieved by those corporations that are able to effectively organize their activities for a long-term (strategic) period. To organize effective strategic management and the formation mechanism of the implementation of development strategies of the Corporation are encouraged to use project-based approach involving activities by initiating, designing, implementing and maintaining projects and programs of the Corporation, provide design controls created by attracting specialists with the necessary competencies in this area. Justifying the expediency of using the project approach, the article describes some general approaches to the organization of such structures, considers their tasks and functions. For organizations (corporations) that aim to achieve long-term success, it is absolutely necessary to find and master methods of managing their own development that provide them with competitive advantages and ensure faster growth rates in the field of activity or industry of the economy. The article is aimed at specialists interested in the management problems of modern socio-economic systems.